Extremely Low Frequency Magnetic Fields Do Not Affect LTP-Like Plasticity in Healthy Humans - Capone, Fioravante; Pellegrino, Giovanni; Motolese, Francesco; Rossi, Mariagrazia; Musumeci, Gabriella; Di Lazzaro, Vincenzo (Frontiers in Human Neuroscience, 2020)
Introduction: Several studies explored, in vitro, the biological effects of extremely low-frequency magnetic fields (ELF-MFs) and reported the induction of functional changes in neuronal activity. In particular, ELF-MFs can influence synaptic plasticity both in-vitro and in animal models. Indeed, some studies reported an increase in long-term potentiation (LTP) whereas others suggested its reduction. However, no specific study has investigated such effect in humans. Aims: To evaluate whether ELF-MFs affect the propensity of the human cortex to undergo LTP-like plasticity. Methods: We designed a randomized, single-blind, sham-controlled, cross-over study on 10 healthy subjects. Cortical plasticity was induced by intermittent theta burst stimulation (iTBS) before and after 45-min ELF-MFs (75Hz;1.8mT) or sham exposure and was estimated by measuring the changes of motor evoked potentials (MEP) amplitude before and after each iTBS. Results: No adverse events were reported. No significant effects of ELF-MFs on cortical plasticity were found. Conclusion: Whole-brain exposure to ELF-MFs (75Hz;1.8mT) is safe and does not seem to significantly affect LTP-like plasticity in human motor cortex.